Biological Complexities in Radiation Carcinogenesis and Cancer Radiotherapy: Impact of New Biological Paradigms - Mozdarani, Hossein (MDPI, 2012)
Although radiation carcinogenesis has been shown both experimentally and epidemiologically, the use of ionizing radiation is also one of the major modalities in cancer treatment. Various known cellular and molecular events are involved in carcinogenesis. Apart from the known phenomena, there could be implications for carcinogenesis and cancer prevention due to other biological processes such as the bystander effect, the abscopal effect, intrinsic radiosensitivity and radioadaptation. Bystander effects have consequences for mutation initiated cancer paradigms of radiation carcinogenesis, which provide the mechanistic justification for low-dose risk estimates. The abscopal effect is potentially important for tumor control and is mediated through cytokines and/or the immune system (mainly cell-mediated immunity). It results from loss of growth and stimulatory and/or immunosuppressive factors from the tumor. Intrinsic radiosensitivity is a feature of some cancer prone chromosomal breakage syndromes such as ataxia telangectiasia. Radiosensitivity is manifested as higher chromosomal aberrations and DNA repair impairment is now known as a good biomarker for breast cancer screening and prediction of prognosis. However, it is not yet known whether this effect is good or bad for those receiving radiation or radiomimetic agents for treatment. Radiation hormesis is another major concern for carcinogenesis. This process which protects cells from higher doses of radiation or radio mimic chemicals, may lead to the escape of cells from mitotic death or apoptosis and put cells with a lower amount of damage into the process of cancer induction. Therefore, any of these biological phenomena could have impact on another process giving rise to genome instability of cells which are not in the field of radiation but still receiving a lower amount of radiation. For prevention of radiation induced carcinogenesis or risk assessment as well as for successful radiation therapy, all these phenomena should be taken into account.